The motivating factors of Malaysian youths political participation - an overview - Samsi, Abdul Hadi; Ab Rahman, Amaludin; Ku Samsu, Ku Hasnita (Elixir, 2013)
Currently it is observed that political participation by youth in Malaysia is increasingly less well received, this is because most of these people are more focused on their studies and their careers. Therefore this paper will discuss the factors that influence the political participation of youth in Malaysia. Among the factors that are highlighted are the Demographic factors, Leadership and Management Factors, the factor of the Leaders’ Communication, Mass Media Factors and Social Environmental Factors that consists of Family Influence, Peer Influence and Influence of the Local Community. From these factors, to a certain extent we are able to more or less see in detail the problems that exist in the political participation of youth, which can also provide some input in the best way to encourage political participation of youth in Malaysia.